Soil Seed Banks, Alternative Stable State Theory, and Ecosystem Resilience. (3rd March 2021) - Ma, Miaojun; Collins, Scott L; Ratajczak, Zak; Du, Guozhen
Abstract: In restoration ecology, the transition from desired to degraded state is based solely on the composition of the aboveground plant community, whereas belowground propagules are often neglected. We developed a conceptual framework integrating seed bank dynamics into alternative stable state theory, highlighting the important relationship between aboveground and belowground composition. This integration emphasizes the role of resilience in systems that appear to have shifted to an "undesirable" state. Belowground propagules, especially soil seed and bud banks, provide buffering capacity and may serve as valuable indicators of potential resistance to state transition based on the degree of similarity between belowground and aboveground vegetation composition. Ecosystem states may have multiple components that differ in their rate of change, as well as in their capacity to promote resilience. We recommend that the application of alternative stable state theory from a management perspective should incorporate components of both above- and belowground vegetation.